A hemispherical near‐field focusing antenna for non‐metallic delamination detection. Issue 12 (26th October 2022) - Yang, Xiaoqing; Long, Shanshan; Su, Piqiang; Xie, Yi; Zhai, Xiaoyu; Dong, Hexin; Li, Meng; Wang, Xueliang
Abstract: This paper proposes a novel hemispherical near‐field focusing radial line slot array (RLSA) antenna to detect delamination within non‐metallic composites. By adjusting the positions and dimensions of the antenna slots, the near‐field focusing antenna produced a radiation pattern with a narrow beamwidth and a low side lobe level of the normal component of the electric field. Since the electromagnetic (EM) field of the near‐field focusing antenna can be focused on the material under test (MUT), delamination within it will significantly affect the reflected information of the antenna. Simulation and measurement have shown the good focusing characteristics of the novel RLSA antenna, a low side lobe level (−19 dB) and a narrow beamwidth (6 mm) were attained. Taking glass fiber reinforced polymer (GFRP) sheets as MUTs, delamination with different thicknesses are detected using a set of mechanical scanning experimental devices. The results show that delamination as thin as 30 μm can be detected. The proposed near‐field focusing antenna can detect thinner delamination inside non‐metallic composites at a lower cost and in a simpler way than other microwave non‐destructive testing (NDT) methods.